Evaluation of the Master's program in Communication Sciences: from context to curricular design, from management to prospective changes: Evaluation of the Master's program in Communication Sciences: from context to curricular design, from management to prospective changes - Sulbarán Piñeiro, Eugenio (Quórum Académico, 2022)
This research aimed to evaluate the current status of the Master's Degree in Communication Sciences at the University of Zulia and its academic-administrative repercussions from 2006 to 2018; focused on the suggestions and contributions of Velazco et al. (2008) regarding the systematization of the analysis, in addition to the results of the study by Coronado (2017). The methodology was triangulated between the deductions of a focus group; interviews with active participants, graduates, professors and postgraduate administrative staff along with the SWOT analysis. The results highlight the incidences of the politicaleconomic-social context of the country in the development of the curriculum, the inconsistency between the objectives of the program and the expectations of the participant and the creation of a new degree.